PENGARUH PEMBELAJARAN KOOPERATIF MODEL TEAM GAMES TOURNAMENT BERBANTU QUIZIZZ TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV - Farah Khansa Baidha; Ferina Agustini; Henry Januar Saputra; Trinil Wigati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to analyze the average difference in the scores of pretest and posttest learning outcomes in Mathematics learning of fourth grade students of SDN Panggung Lor Semarang before and after using the Teams Games Tournaments (TGT) learning model assisted by Quizziz media. The research design used quantitative experiments, namely Pre-Experimental Design with the One-Group Pretest-Posttest Design model. Data obtained through the written test method. The location of this research was carried out in class IV SDN Panggung Lor Semarang. The sample in this study were 29 fourth grade students using saturated sampling technique. The results showed that the results of the paired t-test statistical test showed that there was a difference in the average pretest score of 65, while the average posttest score was 81. It can be seen that the average posttest of students' numeracy test scores is greater than the average. pretest, then Ho is rejected and Ha is accepted. So, there is a difference in the average pretest and posttest scores of students before and after using the Teams Games Tournaments (TGT) model assisted by Quizziz media on Mathematics learning outcomes of fourth grade students at SDN Panggung Lor Semarang.